Gender-Inclusive Public Space Planning through Online Media Planning at Khao San Road Tourist Attraction - Pastraporn Thipayasothorn; Komol Prompeng; Piyanuch Sonsuphap; Manas Ruamruay; Siriporn Rojanasukanjana; Pornthip Techasomburanakit (My University, 2025)
The study of Gender-Inclusive Public Space Planning through Online Media Planning at Khao San Road Tourist Attraction aims to 1) examine the local identity and public service planning for the LGBTQ+ community; 2) design and co-develop the public service area plans to promote the rights of the LGBTQ+ community; and 3) promote the local public space planning policies to promote the rights of the LGBTQ+ community. The study conducted a literature review on the social benefits of online media management, focusing on the concepts of gender diversity and gender-inclusive public spaces such as gender-neutral restrooms. The study was conducted starting from selecting the research site, which was Khao San Road in Bangkok; examining research activities, population and sampling, experts, and LGBTQ+ individuals in Bangkok; designing research instruments including the interview and questionnaire; analyzing data; and presenting the design of local public service area. The findings indicated that the implementation of gender-inclusive public spaces through online media planning at Khao San Road, Bangkok has led to a growing acceptance of the LGBTQ+ community in the Thai society. The legalization of same-sex marriage further reflects this societal acceptance towards inclusivity in public spaces. However, the study highlights a gap in information dissemination, particularly in the tourist area Khao San Road. Therefore, promoting public services through online media planning and providing online information about public services should be considered as a sustainable policy for sustainably managing public spaces in tourist destinations and other communities.
Keywords: BIM and Construction Integration; 3D Modeling in Geospatial Applications